Numerical solution to the Bloch equations： paramagnetic solutions under wideband continuous radio frequency irradiation in a pulsed magnetic field - 陈文俊 马洪 余德 曾小虎 (Chinese physics C, 2016)
A novel nuclear magnetic resonance （NMR） experimental scheme, called wideband continuous wave NMR （WB-CW-NMR）, is presented in this article. This experimental scheme has promising applications in pulsed magnetic fields, and can dramatically improve the utilization of the pulsed field. The feasibility of WB-CW-NMR scheme is verified by numerically solving modified Bloeh equations. In the numerical simulation, the applied magnetic field is a pulsed magnetic field up to 80 T, and the wideband continuous radio frequency （RF） excitation is a band-limited （0.68-3.40 GHz） white noise. ~lrthermore, the influences of some experimental parameters, such as relaxation time, applied magnetic field strength and wideband continuous RF power, on the WB-CW-NMR signal are analyzed briefly. Finally, a multi-channel system framework for transmitting and receiving ultra wideband signals is proposed, and the basic requirements of this experimental system are discussed. Meanwhile, the amplitude of the NMR signal, the level of noise and RF interference in WB-CW-NMR experiments are estimated, and a preliminary adaptive cancellation plan is given for detecting WB-CW-NMR signal from large background interference.